The use of the Karelian language online: Current trends and challenges - Moshnikov, Ilia (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2022)
This article looks to analyze the use of the Karelian language on the internet and especially on social media platforms. The study is based on a survey carried out among Karelian speakers at the end of 2021. The survey was implemented in the Karelian language and received 161 responses, mostly from Finland, but also fromRussia and other countries. The survey consists of questions related to the use of Karelian in daily life and online. The benefits, challenges, and needs related to the use of Karelian online are also explored. The results show that 40% of the respondents use the Karelian language online on a daily basis. Karelian is visible on all of the popular social media platforms, with the most popular being Facebook and Instagram, although the use of TikTok is still rare. However, it is considered that popular social media platforms would benefit from more content in Karelian, in order to support the visibility and revitalization of the Karelian language. Kokkuvõte. Ilia Moshnikov: Karjala keele kasutus veebis: hetkeseis ja väljakutsed. Artikkel analüüsib karjala keele kasutust internetis, keskendudes eriti sotsiaalmeedia platvormidele. Uurimus põhineb andmetel, mis on kogutud karjala keele kõnelejatelt 2021. a lõpus. Küsitlusele vastas 161 informanti, peamiselt Soomest, aga ka Venemaalt ja mujalt. Küsitlus oli koostatud karjala keeles. Esitatud küsimused puudutavad karjala keele kasutamist igapäevaelus ja veebis. Uuritakse ka seda, mida peetakse karjala keele veebis kasutamisel kasulikuks, mida aga väljakutseks, samuti vajadusi, mis karjala keele veebis kasutamisel esile tõusevad. Tulemused näitavad, et 40% vastanutest kasutab karjala keelt veebis igapäevaselt. Karjala keel on esil kõikidel populaarsetel sotsiaalmeedia platvormidel, mille hulgast tõusevad esile Facebook ja Instagram. Seevastu TikTokis kasutatakse karjala keelt veel harva. Peetakse vajalikuks, et populaarsetel sotsiaalmeedia platvormidel oleks rohkem karjalakeelset sisu, sest see toetaks karjala keele nähtavust ja revitalisatsiooni.